Taksonomijos reglamento įtaka aplinkosauginiams mokesčiams Lietuvoje - Jokubauskas, Audrius; Janušauskaitė, Kamilė (Vilnius University Open Series, 2024)
From being an object of scientific discussions climate change has found its way to our everyday lives. It has become an inevitable driver for political decisions. On December 11, 2019 the European Union presented its Green Deal, an action plan to attain sustainable development goals as adopted by the UN General Assembly on September 25, 2015, and in the Paris climate agreement. The EU seeks to become climate-neutral by 2050. A core element of the Green Deal is a system for sustainable finance for climate-friendly economic activities. A common vocabulary is needed in order to eveluate the scope of such economic activities, to balance the input of private and public bodies, and to ensure a fair competition for the investments. Such a vocabulary, also known as Taxonomy, is presented by the Regulation (EU) 2020/852 of the European Parliament and of the Council. It introduces labels and criteria that allow to identify and compare economic activities in the light of sustainability. Eventhough the Taxonomy regulation is a legal act of direct application, it manages to introduce norms into the laws passed by the Lithuanian Parliament. The duty to disclose information on the environmental sustainability of economic activities and investment products comes into force in 2023. Seeking to transform the markets, tax cuts are introduced for economic activities that are in line with the environmental goals. This article unfolds the concept of Taxonomy as well as its impact on investment and tax legislation in Lithuania.